High viral abundance as a consequence of low viral decay in the Baltic Sea redoxcline. - Nicole Köstner; Lisa Scharnreitner; Klaus Jürgens; Matthias Labrenz; Gerhard J Herndl; Christian Winter (PLoS ONE)
Throughout the Baltic Sea redoxcline, virus production and the frequency of lytically-infected prokaryotic cells were estimated from parallel incubations of undiluted seawater and seawater that contained prokaryotes with substantially reduced numbers of viruses (virus dilution approach), effectively preventing viral reinfection during the incubation period. Undiluted seawater incubations resulted in much higher estimates of virus production (6-35×104 mL-1 h-1) and the frequency of infected cells (5-84%) than the virus dilution approach (virus production: 1-3×104 mL-1 h-1; frequency of infected cells: 1-11%). Viral production and the frequency of infected cells from both approaches, however, cannot be directly compared, as data obtained from undiluted incubations were biased by viral reinfection and other uncontrollable processes during the incubation period. High in situ viral abundance (1-2×107 mL-1) together with low virus production rates based on the virus dilution approach resulted in some of the longest viral turnover times (24-84 d) ever reported for the epipelagial. Throughout a wide range of environmental conditions, viral turnover time and burst size were negatively correlated. Given that viral decay estimated in ultra-filtered water was below the detection limit and the burst size was low (1-17), we conclude that prokaryotic viruses in the Baltic Sea redoxcline are investing most of their resources into stress defense (strong capsids) rather than proliferation (high burst size). In summary, the Baltic Sea redoxcline constitutes an environment where low virus production is found in combination with low viral decay, resulting in high viral abundance.